Higher Education in Brazil and the New Administration: What Is at Stake? - Pedrosa, Renato; Knobel, Marcelo (International Higher Education, 2024)
Science and higher education in Brazil have suffered greatly over the past few years, and the new administration of president Lula has promised to bring back the budgets of federal universities to historical levels and to make a strong effort toward social inclusion in higher education. We highlight the main funding-related issues, and also discuss efforts toward social inclusion, such as affirmative action programs and the revisited 2012 national quota law.